Interaction and transaction : a study of conciliar behaviour in a Black South African township - De Jongh, Michael (Rhodes University, Faculty of Humanities, Department of Anthropology, 1980)
The recent history of Africa is one of rapid chance. This process is still continuing and even accelerating. The peoples of Africa are being drawn from a subsistence way of life to a money economy and, more often than not, from a rural to an urban environment. South Africa is no exception to this pattern. In fact, as the most developed country on the continent it is in the front-line of this transformation. Various facets of this problem have held the attention of anthropologists world-wide. Southern Africa specifically has produced some of the earliest urban studies (Hellman, 1948), as well as some of the classical contributions to the field (Mitchell, 1956, 1960, 1966, 1969, 1970; Epstein, 1958; Mayer, 1961, "(1971), 1962; Pauw, 1963). Complex as the urban problems are, anthropologists have obviously not been alone in this field. Workers from many disciplines have been and still are required to contribute to the understanding of the process or urbanization as well as the urban process. Partly for this reason no attempt has been made in the present study to illuminate all the varied facets of the urban field. In general, the focus has been on the urban process and more specifically, on part of a local-level political system. Thus only a limited problem has been selected for analysis.
Keywords: Social interaction -- South Africa -- Port Elizabeth; Black people -- South Africa -- Politics and government; Local government -- South Africa -- Eastern Cape